The Plastic Waste Crisis in the Modern Era as a Moral Problem: A Review of Environmental Philosophy on People's Consumption Behavior - Munawaroh Muna Muna (Al-Imtaz: Jurnal Keilmuan Ushuluddin, 2026)
The plastic waste crisis in the modern era is a global environmental problem that not only impacts ecosystem degradation but also reflects a moral crisis in society's consumption behavior. The increasing use of single-use plastics, driven by practical lifestyles and consumerist culture, has exacerbated the accumulation of non-biodegradable waste, posing a serious threat to environmental sustainability. This study aims to analyze the plastic waste crisis as a global moral problem through the perspective of environmental philosophy, emphasizing the relationship between humans and nature and its implications for consumption behavior. The method employed is a qualitative approach through literature study, examining various environmental ethical theories such as anthropocentrism, biocentrism, and ecocentrism. The expected findings indicate that the dominance of the anthropocentric paradigm has encouraged exploitative and unsustainable consumption patterns, while biocentric and ecocentric approaches offer alternative ethical frameworks that are more holistic in maintaining ecosystem balance. Furthermore, this study suggests that transforming consumption behavior requires a shift in moral awareness grounded in ecological values. Therefore, the plastic waste crisis should not only be understood as a technical issue but also as an ethical crisis that demands a paradigm shift, collective responsibility, and the adoption of sustainable lifestyles.